Risk of Reactivation of Hepatitis B in Hepatitis B Surface Antigen-Negative and Hepatitis B Core Antigen Antibody Positive Patients Receiving Biologic Therapy - Gök Sargın, Zeynep (Turkish Journal of Gastroenterology, 2023)
Cite this article as: Gök Sargın Z. Risk of reactivation of hepatitis B in hepatitis B surface antigen-negative and hepatitis B core antigen antibody positive patients receiving biologic therapy. Turk J Gastroenterol. 2023;34(3):308-309.